Attitudes towards code-switching in Malay Television series and own tendency to code-switch - Ting, Su Hie; Muriatul Khusmah, Musa (2014)
Code-switching is an inherent feature of language use, particularly among certain quarters of the speech community in multilingual settings. As a reflection of the multilingual characteristics of the Malaysian speech community, some Malaysian television series are showing use of code-switching in their shows. This study examined whether Malaysian youths' perception of the acceptability of code-switching in Malay television series is linked to their own tendency to code-switch. A short video clip of a Malay television series with code-switching was shown before the university students filled in the questionnaires. The results from 141 university students indicated that the Malay students code-switched more frequently than non-Malay students and were more receptive towards code-switching in Malay television series. However, they were similar in their views on the negative implications of incorporating code-switching in Malay television series. The results show that Malay speakers who code-switch from Malay to English are likely to be perceived as educated, modern and rich and, at the same time, they are seen as “showing off”. In the context of language learning, code-switching is also viewed as a compensatory strategy in the face of communication breakdown.